2015
DOI: 10.2495/sd150271
|View full text |Cite
|
Sign up to set email alerts
|

EMAS: unfulfilled expectations and challenges associated with the planned publication of the new ISO 14001:2015

Abstract: The reconciliation of economic growth with environment is currently one of the biggest challenges facing Europe and the world. Demand for natural resources is growing, and global competition in this field causes an increase in pressure on the environment. The necessity of efficient usage of resources entails the need for changes in production models. In this regard, implementing of environmental management systems (EMS) such as international normalized ISO 14001 or European EMAS (Eco-management and Audit Schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The negative trend may be attributed to a lack of resources for environmental investment [2,3] and the short-term orientation of many organisations, considering that environmental investments generally have a long-term return [4]. Many organisations registered under the EMAS scheme do not renew their registrations, because, among other reasons, they do not achieve the expected benefits in relation to the expenditures and outlays, they have problems updating the environmental statement, they do not receive regulatory concessions such Energies 2022, 15, 434 2 of 14 as tax reliefs and, in general, they are disappointed by the lack of incentives from the member states and public administration [2,5,6]. Moreover, developed by the International Organisation for Standardisation (ISO), the environmental management system based on ISO 14001 is over 100 times more popular than EMAS, with 396,242 valid ISO 14001 certificates issued worldwide, including 92,828 in Europe and 3766 in Poland [7].…”
Section: Introductionmentioning
confidence: 99%
“…The negative trend may be attributed to a lack of resources for environmental investment [2,3] and the short-term orientation of many organisations, considering that environmental investments generally have a long-term return [4]. Many organisations registered under the EMAS scheme do not renew their registrations, because, among other reasons, they do not achieve the expected benefits in relation to the expenditures and outlays, they have problems updating the environmental statement, they do not receive regulatory concessions such Energies 2022, 15, 434 2 of 14 as tax reliefs and, in general, they are disappointed by the lack of incentives from the member states and public administration [2,5,6]. Moreover, developed by the International Organisation for Standardisation (ISO), the environmental management system based on ISO 14001 is over 100 times more popular than EMAS, with 396,242 valid ISO 14001 certificates issued worldwide, including 92,828 in Europe and 3766 in Poland [7].…”
Section: Introductionmentioning
confidence: 99%
“…adaptation to climate change) are considered. It has been argued that the updated ISO14001 standard is moving towards the more rigorous EMAS system, and is more difficult to achieve (Szyszja & Matuszak-Flejszmann, 2015) with better environmental gains over the longer term (Testa et al, 2014). These formal systems also typically include aspects and impacts that are deemed to be measurable and manageable, and may exclude some of the wider environmental and sustainability aspects with less tangible metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies have shown that operating EMAS in Poland has appeared to be disappointing in many cases [22]. Unfulfilled expectations concern mainly financial and economic aspects (no tax relief and reduction of insurance rates, no influence on environmental fees, no priority in obtaining grants and subsidies).…”
Section: Recommendationsmentioning
confidence: 99%